2013
DOI: 10.1088/0031-9155/58/20/7209
|View full text |Cite
|
Sign up to set email alerts
|

Design and performance evaluation of a 20-aperture multipinhole collimator for myocardial perfusion imaging applications

Abstract: Single photon emission computed tomography (SPECT) myocardial perfusion imaging (MPI) remains a critical tool in the diagnosis of coronary artery disease (CAD). However, after more than three decades of use, photon detection efficiency remains poor and unchanged. This is due to the continued reliance on parallel-hole collimators first introduced in 1964. These collimators possess poor geometric efficiency. Here we present the performance evaluation results of a newly designed multipinhole collimator with 20 pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…The pin-hole collimation has been introduced to compensate the low photon detection efficiency of parallel-hole systems and to improve the image contrast [11,17]. The collimator consists of a single hole drilled into a lead sheet [6,20].…”
Section: Pin-hole Collimatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pin-hole collimation has been introduced to compensate the low photon detection efficiency of parallel-hole systems and to improve the image contrast [11,17]. The collimator consists of a single hole drilled into a lead sheet [6,20].…”
Section: Pin-hole Collimatorsmentioning
confidence: 99%
“…There has been much improvement in collimator geometry and also reconstruction algorithms [7,8,[10][11][12]. Parallel hole collimator is routinely used to planar and SPECT imaging [13][14][15][16][17]. An array of holes separated by thin walls (septa), which are fabricated by employing heavy elements, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of scatter and parallax were not included in the system matrix. 29 Finally, all reconstructed images were postprocessed with a low-pass order 10 Butterworth filter with 0.7 cycles per pixel (pixel size of 0.368 cm) as previously suggested 9,10 and to match the postfiltering used in the vendor provided software for LEHR OSEM reconstruction of the brain. This postfilter helps to remove high frequency noise that may be a result of the acquisition or reconstruction.…”
Section: B Experimental Setups Image Acquisitions and Reconstructmentioning
confidence: 99%
“…In our recent study inspired by an earlier work by Funk, 28 we reported the performance test of the multipinhole collimation and showed that the new 20-pinhole collimator improves the SNR of myocardial perfusion imaging (MPI) by a factor greater than 2 over that of using LEHR collimators with a fixed resolution of 12.5 mm. 29 The purpose of this study was to investigate the performance of a new 20 multipinhole (20-MPH) collimator over the conventional LEHR technology for brain SPECT imaging and to perform physical experimental measurements with the 20-MPH. Our working hypothesis was that a substantial improvement in counting statistics (signal-to-noise, efficiency, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…11 However, for human cardiac studies, the multipinhole system operates in minification mode, that is, the object is placed away from the pinhole and the images on the detector are smaller than the object [ Fig. 1(b)], e.g., UC San Francisco and Western Cardiology Associate's stationary multipinhole system 7,8,12 and Discovery NM 530c (GE Healthcare, Haifa, Israel). 9,10 The detection sensitivity is proportional to the image magnification factor.…”
Section: Introductionmentioning
confidence: 99%